Direct measurement of oxygen reduction reactions at neurostimulation electrodes - Ehlich, Jiří; Migliaccio, Ludovico; Sahalianov, Ihor; Nikić, Marta; Brodský, Jan; Gablech, Imrich; Vu, Xuan Thang; Ingebrandt, Sven; Głowacki, Eric Daniel (Journal of neural engineering, 2022)
Objective. Electric stimulation delivered by implantable electrodes is a key component of neural engineering. While factors affecting long-term stability, safety, and biocompatibility are a topic of continuous investigation, a widely-accepted principle is that charge injection should be reversible, with no net electrochemical products forming. We want to evaluate oxygen reduction reactions (ORR) occurring at different electrode materials when using established materials and stimulation protocols.Approach. As stimulation electrodes, we have tested platinum, gold, tungsten, nichrome, iridium oxide, titanium, titanium nitride, and poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate). We use cyclic voltammetry and voltage-step amperometry in oxygenated versus inert conditions to establish at which potentials ORR occurs, and the magnitudes of diffusion-limited ORR currents. We also benchmark the areal capacitance of each electrode material. We use amperometric probes (Clark-type electrodes) to quantify the O2and H2O2concentrations in the vicinity of the electrode surface. O2and H2O2concentrations are measured while applying DC current, or various biphasic charge-balanced pulses of amplitude in the range 10-30µC cm-2/phase. To corroborate experimental measurements, we employ finite element modelling to recreate 3D gradients of O2and H2O2.Main results. All electrode materials support ORR and can create hypoxic conditions near the electrode surface. We find that electrode materials differ significantly in their onset potentials for ORR, and in the extent to which they produce H2O2as a by-product. A key result is that typical charge-balanced biphasic pulse protocols do lead to irreversible ORR. Some electrodes induce severely hypoxic conditions, others additionally produce an accumulation of hydrogen peroxide into the mM range.Significance. Our findings highlight faradaic ORR as a critical consideration for neural interface devices and show that the established biphasic/charge-balanced approach does not prevent irreversible changes in O2concentrations. Hypoxia and H2O2can result in different (electro)physiological consequences.
Keywords: elektrická stimulace; platina; Electric Stimulation; Hydrogen Peroxide; Platinum; Hypoxia; neurostimulation; Electrodes, Implanted; reactive oxygen species; hypoxia; lidé; peroxid vodíku; faradaic reactions; hypoxie; bioelectronics; Electrodes; Oxygen; implantované elektrody; elektrody; kyslík; Humans